2012
DOI: 10.1002/jsfa.5721
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature conditioning induces chilling tolerance in mandarin fruit: a cell wall approach

Abstract: High-temperature conditioning may reduce chilling-induced flavedo pitting in 'Fortune' mandarin fruit by maintaining normal levels of WSP and increasing putative sites for calcium bridge formation within the cell wall, but not by inducing changes in other matrix cell wall components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 62 publications
(95 reference statements)
0
3
0
2
Order By: Relevance
“…However, low 1-MCP levels may reduce the incidence of the disorder in other citrus cultivars (Salvador et al, 2006). Other results have shown that ethylene production transiently increases at 37°C during the 3-day conditioning treatment (Holland et al, 2012), which markedly reduces CI. However, the conditioning treatment prevented the rise in ethylene that occurs in non-conditioned fruits in response to chilling, which was much higher than that induced at 37°C (Holland et al, 2012).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, low 1-MCP levels may reduce the incidence of the disorder in other citrus cultivars (Salvador et al, 2006). Other results have shown that ethylene production transiently increases at 37°C during the 3-day conditioning treatment (Holland et al, 2012), which markedly reduces CI. However, the conditioning treatment prevented the rise in ethylene that occurs in non-conditioned fruits in response to chilling, which was much higher than that induced at 37°C (Holland et al, 2012).…”
Section: Resultsmentioning
confidence: 84%
“…Other results have shown that ethylene production transiently increases at 37°C during the 3-day conditioning treatment (Holland et al, 2012), which markedly reduces CI. However, the conditioning treatment prevented the rise in ethylene that occurs in non-conditioned fruits in response to chilling, which was much higher than that induced at 37°C (Holland et al, 2012). This result might suggest that during the 3 days that the conditioning treatment at 37°C lasts, some defense mechanism against chilling is initiated and, therefore, the cold-induced increase in ethylene is not necessary to cope with stress or to contain lesion propagation in tissues that present CI.…”
Section: Resultsmentioning
confidence: 84%
“…Temperatures higher than 50 ºC increased the heat damage in the epidermis, indicating the importance of the temperature and immersion time in hot water as determining factors of the efficiency of the thermal treatment. According to Sevillano et al (2009) and Holland et al (2012), prolonged times and higher temperatures of thermal treatment with water may produce negative effects on the fruit quality. However, both the treatment time and temperature depend on the species, size and maturity stage, among other factors (Ma et al 2014).…”
Section: Abstract Resumomentioning
confidence: 99%
“…Investigadores como Ghasemnezhad et al (2008) en mandarina 'Satsuma', encontraron resultados favorables con agua a 47,5ºC por 2 o 5 min y con agua a 50ºC por 2 min. De acuerdo con Holland et al (2012) tiempos prolongados y altas temperaturas del tratamiento térmico con agua pueden generar efectos negativos en la calidad de los frutos. No obstante, tanto el tiempo como la temperatura del tratamiento dependerá de la especie, el tamaño, estado de madurez, entre otros (Ma et al, 2014).…”
unclassified